Miocene dinoflagellate cyst assemblages: preliminary correlation between the Lower Tagus and Algarve Basins (Portugal) - Castro, Lígia (2013)
Biostratigraphic studies of several sections and a borehole (Belverde) of the Lower Tagus Basin, based on Miocene dinoflagellate cyst assemblages, have allowed a detailed stratigraphic investigation to be conducted. Assemblages are very diverse and abundant and can be used as important biostratigraphic guides. Recently, a palynostratigraphic study based on dinoflagellate cysts was conducted in two offshore wells, Ruivo-1 and Corvina, located in the Algarve Basin (southern Portugal). The recovered dinoflagellate assemblages are less abundant and diverse than those obtained in the Lower Tagus Basin. New inferences are made regarding the correlation between the dinoflagellate cysts known from the Lower Tagus Basin with the assemblages recently recovered from the Algarve Basin. Species of selected dinoflagellate cyst assemblages recovered are similar in both basins. Continuing progress with these new palynological studies and biostratigraphic data will help to refine knowledge of and correlations between Portuguese Miocene deposits.